A new spectrophotometric method for the determination of fluvoxamine maleate in pure form and in pharmaceutical formulation - Saravanan Devarajan, Gobinath Manavalan, Kumar Balasubramanian, Jayakumar Annamalai, Narasimhakumar Madduri (Journal of Applied Pharmaceutical Science, 2015)
A simple, accurate and highly sensitive spectrophotometric methods are proposed for the rapid and accurate determination of fluvoxamine maleate (FXA) using bromocressol green (BCG), methyl orange (MO) and bromothymol blue (BTB). The developed methods involve formation of stable yellow colored chloroform extractable ion-associate complexes of the amino derivative (basic nitrogen) of the FXA with three sulphonphthalein acid dyes, namely; BCG, MO and BTB, in potassium hydrogen phthalate buffer pH 3.3, 3.6 and 3.4 respectively. The ion-associates exhibit absorption maxima at 420, 420 and 410 nm for BCG, MO and BTB, respectively. FXA can be determined up to 2.0–16, 2.0–15 and 2.0–20 µgmL−1 for BCG, MO and BTB, respectively. The effect of optimum conditions via pH on the ion pair formation, reagent concentration, time and temperature, and solvent was studied. The composition of the ion pairs was found 1:1 by Job’s method. The low relative standard deviation values indicate good precision and high recovery values. These methods have been successfully applied for the assay of FXA in pure form and in pharmaceutical formulations and the results are in good agreement with those obtained by the official method.
Keywords: FXA, Bromothymol blue, Methyl orange,Bromocresol green, Ion-pair complex.